Trend Hipertensi Maternal - Chaneda Naela Karima; Sani Rahman Soleman; Vita Widyasari (Pusat riset dan Inovasi Nasional, 2026)
Maternal hypertension remains one of the major contributors to maternal morbidity and mortality in Indonesia and globally. This study aimed to analyze the prevalence, mortality trends, and geographical disparities of maternal hypertension in Indonesia during the 2022–2023 period. The research employed a descriptive design using secondary data obtained from official reports of the Indonesian Ministry of Health, national health surveys, and Maternal Perinatal Death Notification (MPDN) data. Data analysis was conducted descriptively by examining prevalence rates, maternal mortality due to hypertension, regional distribution, and temporal trends across provinces in Indonesia. The findings showed a slight but consistent decline in both the prevalence and mortality rates of maternal hypertension from 2022 to 2023 in most provinces. However, significant regional disparities remained evident. Provinces in eastern Indonesia, including Papua Barat, Nusa Tenggara Timur, Maluku, and several provinces in Sulawesi and Kalimantan, consistently recorded higher prevalence and mortality rates compared to provinces in Java and Bali. Meanwhile, provinces with better healthcare infrastructure and maternal referral systems demonstrated lower mortality outcomes. The study also revealed a strong association between high prevalence and increased maternal mortality, indicating the importance of healthcare accessibility, antenatal care quality, and emergency obstetric services in reducing maternal health burdens. These findings emphasize the need for region-specific maternal health interventions, improved healthcare distribution, early detection programs, and strengthened referral systems to reduce maternal hypertension disparities and improve maternal health outcomes in Indonesia.